Process modelling and thermodynamic analysis of hydrogen production through chemical looping ammonia cracking - Soman, Anantha Krishnan Vinayak; Wang, Siqi; Shen, Ziqi; Zhu, Mingming (Royal Society of Chemistry (RSC), 2025)
In this study, a novel chemical looping ammonia cracking (CLCr) process was designed for efficient hydrogen production. A closed-loop, three-reactor chemical looping system using iron oxide as the oxygen carrier was modelled in Aspen Plus. A parametric study was carried out to evaluate the effect of key parameters, including the air reactor outlet temperature, fuel reactor outlet temperature, ammonia to oxygen carrier ratio, and the steam reactor pressure. The optimal operating conditions were then identified, under which a hydrogen yield of 69.4% with 99.99% purity can be achieved with an overall energy efficiency of 79.6%. An energy balance analysis was also carried out to confirm that the process is autothermal, and the overall exergy efficiency of the process was 70.4%. These findings highlight the novel CLCr process as an energy-efficient alternative to conventional ammonia catalytic cracking for hydrogen production.
Keywords: 40 Engineering; 7 Affordable and Clean Energy; 3406 Physical chemistry; 4004 Chemical engineering; 4008 Electrical engineering